Factor Influencing Outcome of Pyogenic Spondylodiscitis - Chumpon, Kakanan; Luckchai, Ponwijit (Thai Journal of Neurological Surgery, 2025)
Background: Pyogenic spondylodicitis is a rare condition but might be devastating and fatal. Traditional treatment is surgical debridement follow by antibiotics. A retrospective study was designed to assess the effect of clinical findings and treatment methods on the outcome. Material and Metods: 21 patients were reviewed. There were 13 men and 8 women, with age ranging from 24 to 85 years, mean age 61.9 years. 5 patients with complete cord. Pyogenic spondylodicitis found in cervical [12] thoracic [2], lumbar [4] and mutiple [3] regions. The diagnosis was defined by clinical findings, culture, histopathology, and radiological methods such as magnetic resonance imaging [MRI] and computed tomography [CT] scans. All patients received surgical debridement and follow with medication. Results: A total of 21 patients,operative treatment was performed. Surgical debridement with or without instrumentation was done in all cases. After surgical debridement, clinical was improved. The most presenting symptom is spinal pain. All of patients have elevated ESR and CRP. The most common bacterium isolated was Staphylococcus spp. Two motality case was observed. Conclusion: Pyogenic spondylodiscitis should be suspected in people having pain and local tenderness in the spinal region with rise in infalammatory parameters in blood. The most common bacterium was Staphylococcus species, but there were not still a greater number of patients in this study. Therefore, In case with severe neurological deficit, surgical debridement follow by antibiotic therapy is the most effective treatment. Limitation of data is lack of uncontrolled study group.